PENGARUH FAKTOR FUNDAMENTAL TERHADAP NILAI PERUSAHAAN PADA SEKTOR PROPERTI DAN REAL ESTATE - HAQI F, MUHAMMAD; ASANDIMITRA HARYONO, NADIA (Jurnal Ilmu Manajemen (JIM), 2019)
This quantitative research was conducted to analyze the influence of firm size, firm age, dividend policy and capital expenditure on firm value. Since 2012, the property and real estate sector has shown a decline. This continues until 2017 seen from the sales data that has decreased. Whereas in 2015, the government has issued a policy to encourage growth in this sector. Determination of sample using purposive sampling with the criteria include companies in the property and real estate sector that are listed on the IDX and have complete data consistently for the period 2014-2017. Then the sample data obtained 34 companies in a period of 4 years, so that the total number of samples is 136. The results of the study show the firm age and dividend policy significantly influence the firm value. While the firm size and capital expenditure were not found to have an influence on the firm value.